WATER REQUIREMENTS AND WATER USE OF MANGO ORCHARDS IN JAZAN REGION, SAUDI ARABIA - F. S. Mohammad; A. I. Alamoud; S. H. Mahmoud (Journal of Animal and Plant Sciences, 2015)
Assessment of crop water requirement (CWR) is of vital importance in water resources management and planning in Saudi Arabia. In the present study, data of a field experiment carried out atJazan, a semi-arid region of northern region of Saudi Arabia, were used to obtain irrigation requirements and evapotranspiration (ET) of mango orchard growth during three successive seasons (2008 to 2011). The measurements were performed within a randomly selected experimental plot with 8 × 8 m spacing between rows and plants. The soil water balance method was used to obtain the mango water requirements and the Penman–Montieth method (FAO/56) was used to determine reference evapotranspiration (ETr). The soil water content was determined by six tensiometer sets installed at 0.20 m layer intervals from the soil surface down to a 1.20 m soil depth. The experimental plot was irrigated with a drip irrigation system based on soil-moisture status. The results showed that ET was strongly influenced by soil water availability. The comparison between measured and computed ETr revealed higher trends for measured ETr rates, with an average of about 5.9 mm/day. As for the net mango water use, the average daily rates ranged from 0.114m3/tree/day for drip irrigation and 0.172 m3/tree/day for surface irrigation. The total net annual mango water use had an averaged value of 31.63 m3/tree/season while the average annual water requirement for mango was 6527 m3/ha/season under drip irrigation and 9790 m3/ha/season under surface irrigation. The mango crop coefficients ranged between 0.71 and 0.77. From an economic perspective, the variations in the total net annual mango water use in the study areas influenced the average water costs and the net economic returns of mango farms. From an economic perspective, the variations in the total net annual mango water use in the study area influenced the average water costs and the net economic returns of mango farming. The water costs represented about 11% of the average variable costs of mango farming in the study area, whereas the water costs ranged from a minimum of about 678 Saudi riyals per hectare (SR ha-1).
Keywords: Mango water requirement; Crop Coefficient; Lysimeter; Penman–Montieth; Reference Evapotranspiration; Water costs; Net economic returns.